Assessment of heavy metal contamination in water and sediments of Bertam River in Cameron Highlands and its association with ecological and health risks - Razali, Azlini (2019)
Rampant land clearing for agriculture, urbanization, development of hotel and residential areas have rapidly altered the land use setting of Cameron Highlands. Unsustainable development and encroachment of river reserve areas have continuously deteriorated the Bertam River quality. The pollutants from Bertam River also may flow to downstream river network that serves as raw water sources for water treatment plants. Thus, it increases the potential health risk to the population downstream. This study aimed to assess heavy metal contamination in water and sediments of Bertam River in Cameron Highlands and its association with ecological and health risks. The differences in water quality status between Upper and Lower stations as well as seasonal changes were determined. The concentration of aluminium (Al), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), and zinc (Zn) in water and sediment samples were tested via Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The results showed that all studied physicochemical parameters were generally higher at the Lower stations. For example, in the wet season, the turbidity at the Lower stations (191.72 ± 139.78 NTU) was recorded higher than the Upper area (55.77 ± 147.55 NTU). Similarly, total suspended solids (TSS) was higher in the Lower area (158.07 ± 107.71 mg/L) compared to the Upper area (43.98 ± 78.97 mg/L). All physicochemical parameters were within the Malaysian National Drinking Water Quality Standards (NDWQS) except for turbidity, ammoniacal-nitrogen (NH3-N) and Escherichia coli (E. coli). The heavy metal distribution in Upper and Lower stations was varied. Elements such as Iron (Fe), Al, Cu, and Zn were the most prominent and were higher during the wet season. The overall mean concentration of Cd, Fe and Pb exceeded the NDWQS. Seasonal changes do influence some of the river water properties such as dissolved oxygen (DO), turbidity and total suspended solids (TSS) where they were significantly higher during the wet season. The contamination factor (CF), geo-accumulation index (Igeo) and pollution load index (PLI) showed low ecological risk from a bioavailable fraction of heavy metal in the sediment of Bertam River. As for health risk, the carcinogenic risk of Cd in male adult (3.05 x 10-3), female adult (2.97 x 10-3) and children (4.91 x 10-3) were >10-4 which indicates an unacceptable carcinogenic risk. Three main potential pollution sources contributed to river water deterioration in this study were the artificial phosphate fertilizer and agrochemical products, soil erosion and land clearing. While the potential pollution sources in sediment were anthropogenic activities such as agriculture and sand dredging, soil erosion and the adsorption with soil mineral oxides. In conclusion, heavy metal in river and sediment samples were generally low and within acceptable risk to human and ecology except for Cd. Findings from this study have improved our understanding of how the agricultural activities and land use changes could interfere with the ecological niche particularly river networks in this area.